An exploration of hospital pharmacists' attitudes and opinions towards undertaking research. (10th April 2023) - Shenton, Julie; Fitzpatrick, Ray; Gifford, Alison
Abstract: Objectives: This research aimed to explore the attitudes and opinions of hospital pharmacists to undertaking research to understand the drivers, drawbacks, barriers and enablers to engagement and explore the characteristics of research-active pharmacy departments. Methods: A qualitative approach was employed using case study methodology where interviews were undertaken with the chief pharmacist and a cohort of research-active pharmacists at four secondary care NHS Trusts. Each of the four case study sites had high levels of research activity among pharmacists and a model of support for them to undertake research. Key findings: Research experience was identified as a significant driver, as was a pharmacy department having a research culture. Drawbacks identified related to the impact of research on service delivery, and the difficulty associated with backfilling posts with funding from grants. Lack of time, difficulty obtaining funding, lack of personal competence and research not being prioritised were identified as barriers to engagement, as were a lack of understanding and awareness of research and a lack of appreciation of its value. Key enablers included having time to conduct research and having access to individuals with research expertise. Research-active pharmacy departments all had a supportive chief pharmacist, a culture for research and mechanisms of support in place. Conclusions: To increase research engagement among pharmacists in the hospital sector, there needs to be cultural change at a professional level to drive engagement and give individuals the time and skills to be undertake research.